Persistent organohalogen contaminant burdens in Antarctic krill (Euphausia superba) from the eastern Antarctic sector: A baseline study - Bengtson Nash, Susan M; Poulsen, Anita H.; Kawaguchi, So; Vetter, Walter; Schlabach, Martin (Science of the Total Environment, 2008)
A baseline for persistent organohalogen compound (POC) accumulation in the Antarctic keystone species, Antarctic krill (Euphausia superba) has been established for a 50° longitudinal range of the eastern Antarctic sector. Samples of adult krill, caught from 12 sites distributed between 30° and 80°E (60–70°S), were analysed for >100 organohalogen compounds including chlorinated pesticides, polychlorinated biphenyls (PCBs), polybrominated organic compounds and polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs). Organochlorine pesticides dominated measured krill contaminant burdens with hexachlorobenzene (HCB) as the single most abundant compound quantified. Krill HCB concentrations were comparable to those detected at this trophic level in both the Arctic and temperate northwest Atlantic, lending support for the hypothesis that HCB will approach global equilibrium at a faster rate than other POCs. Para, para′-dichlorodiphenylethene (p,p′-DDE) was detected at notable concentrations. Measurements of DDT and its degradation products provide an important baseline for monitoring the temporal and geographical influence of renewed, DDT usage for malaria-control in affected southern hemisphere countries. In contrast to the Arctic, PCBs did not feature prominently in contaminant burdens of Antarctic krill. The major commercial polybrominated diphenyl ether (PBDE) congeners -99 and -47 were quantified at low background levels with clear concentration spikes observed at around 70°E , in the vicinity of modern, active research stations. The likelihood that local anthropogenic activities are supplementing low PBDE levels, delivered otherwise primarily via long range environmental transport, is discussed. The suspected naturally occurring brominated organic compound, 2,4,6-tribromoanisole (TBA), was a ubiquitous contaminant in all samples whereas the only PCDD/Fs quantifiable were trace levels of octachlorodibenzo-p-dioxin (OCDD) and 1,2,3,4,7,8/1,2,3,4,7,9-hexachlorodibenzofuran (HxCDF). With the aims of; i) Generating a robust and broadly applicable POC auditing platform for the scarcely studied eastern Antarctic sector; ii) Determining the compounds accumulating in Antarctic krill for further toxicity evaluation studies and iii) Establishing a baseline for Antarctic predator exposure to POCs, this study represents one of the most comprehensive reports of POC contamination of the Antarctic food web to date.
Keywords: Sørishavet; forurensning; krill; marine økosystemer; menneskelig påvirkning; miljøgifter; plankton; toksikologi

"En livbåt halvfull av vann er funnet". Forlis og ulykker i hvalfangsten på 1920-tallet - Børresen, Dag Ingemar (Norsk sjøfartsmuseum. Årbok, 2008)
Publisher: Norsk sjøfartsmuseum
Keywords: Sørishavet; hvalbåter; hvalfangere; hvalfangstindustri; hvalkokerier; isfangsten; pelagisk; sjøfolk

Southern Ocean frontal structure and sea-ice formation rates revealed by elephant seals - Charrassin, J.-B.; Hindell, M.; Rintoul, S. R.; Roquet, F.; Sokolov, S.; Biuw, M.; Costa, D.; Boehme, L.; Lovell, P.; Coleman, R.; Timmermann, R.; Meijers, A.; et al. (Proceedings of the National Academy of Sciences, 2008)
Polar regions are particularly sensitive to climate change, with the potential for significant feedbacks between ocean circulation, sea ice, and the ocean carbon cycle. However, the difficulty in obtaining in situ data means that our ability to detect and interpret change is very limited, especially in the Southern Ocean, where the ocean beneath the sea ice remains almost entirely unobserved and the rate of sea-ice formation is poorly known. Here, we show that southern elephant seals (Mirounga leonina) equipped with oceanographic sensors can measure ocean structure and water mass changes in regions and seasons rarely observed with traditional oceanographic platforms. In particular, seals provided a 30-fold increase in hydrographic profiles from the sea-ice zone, allowing the major fronts to be mapped south of 60°S and sea-ice formation rates to be inferred from changes in upper ocean salinity. Sea-ice production rates peaked in early winter (April?May) during the rapid northward expansion of the pack ice and declined by a factor of 2 to 3 between May and August, in agreement with a three-dimensional coupled ocean?sea-ice model. By measuring the high-latitude ocean during winter, elephant seals fill a ?blind spot? in our sampling coverage, enabling the establishment of a truly global ocean-observing system.
Publisher: Proceedings of the National Academy of Sciences
Keywords: Sørishavet; havis; hydrografi; klimaendringer; marin biologi; oseanografi; polarområdene; sjøelefanter; sjøis; sjøpattedyr

Regeneration of Fe(II) during EIFeX and SOFeX - Croot, Peter L.; Bluhm, Kathrin; Schlosser, Christian; Streu, Peter; Breitbarth, Eike; Frew, Russell D.; Ardelan, Murat van (Geophysical Research Letters, 2008)
Investigations into Fe(II) cycling during two Southern Ocean mesoscale iron enrichment experiments, SOFeX and EIFeX, clearly show the importance of Fe(II) to iron speciation during these experiments. In both cases the added Fe(II) persisted significantly longer than its expected oxidation time indicating a significant Fe reduction process at work. During EIFeX diel studies showed a strong photochemically induced cycle in Fe(II) production in sunlit surface waters. Our results suggest that the photochemical cycling of iron may also be important in unfertilized waters of the Southern Ocean.
Keywords: Sørishavet; biogeokjemi; fytoplankton; marin biologi; polarområdene

Fast-ice distribution in East Antarctica during 1997 and 1999 determined using RADARSAT data - Giles, A Barry; Massom, Robert A; Lytle, Victoria I (Journal of Geophysical Research: Oceans, 2008)
We present the first detailed maps of fast ice around East Antarctica (75°E–170°E), using an image correlation technique applied to RADARSAT ScanSAR images from November in 1997 and 1999. This method is based upon searching for, and distinguishing, correlated regions of the ice-covered ocean which remain stationary, in contrast to adjacent moving pack ice. Within the overlapping longitudinal range of ∼86°E–150.6°E, the total fast-ice area is 141,450 km2 in 1997 and 152,216 km2 in 1999. Calibrated radar backscatter data are also used to determine the distribution of two fast-ice classes based on their surface roughness characteristics. These are “smooth” fast ice (−25.4 dB to −13.5 dB) and “rough” fast ice (−13.5 dB to −2.5 dB). The former comprises ∼67% of the total area, with rough fast ice making up the remaining ∼33%. An estimate is made of fast-ice volume, on the basis of fast-ice type as a proxy measure of ice thickness and area. Results suggest that although fast ice forms 2–16% of the total November sea ice area for this sector of East Antarctica in 1997 and 1999 (average 8.3% across maps), it may comprise 6–57% of the total ice volume (average ∼28% across maps). Grounded icebergs play a key role in fast-ice distribution in all regions apart from 150°E–170°E. These are “snapshot” estimates only, and more work is required to determine longer-term spatiotemporal variability.
Keywords: Sørishavet; batymetri; biologi; havis; kartlegging; landfast is; satellite bilder; sjøis; økologi

Decline in energy storage in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Tamura, Tsutomu; Zenitani, Ryoko; Bando, Takeharu; Kato, Hidehiro; Walløe, Lars (Polar Biology, 2008)
The annual trend in energy storage in the Antarctic minke whale was examined using catch data from all 18 survey years in the Japanese Whale Research Program (JARPA). Regression analyses clearly showed that blubber thickness, girth and fat weight have been decreasing for nearly 2 decades. The decrease per year is estimated at approximately 0.02 cm for mid-lateral blubber thickness and 17 kg for fat weight, corresponding to 9% for both measurements over the 18-year period. Furthermore, "date", "extent of diatom adhesion", "sex", "body length", "fetus length", "latitude", "age" and "longitude" were all identified as partially independent predictors of blubber thickness. The direct interpretation of this substantial decline in energy storage in terms of food availability is difficult, since no long-term krill abundance series is available. However, an increase in the abundance of krill feeders other than minke whales and a resulting decrease in the krill population must be considered as a likely explanation.
Keywords: Sørishavet; hvaler; krill; marin biologi; plankton; vågehvaler

Crustal structure and tectonic provinces of the Riiser-Larsen Sea area (East Antarctica): results of geophysical studies - Leitchenkov, German; Guseva, J; Gandyukhin, V; Grikurov, G; Kristoffersen, Yngve; Sand, M; Golynsky, A; Aleshkova, N (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; seismologi; stratigrafi

Halo of ice deformation observed over the Maud Rise seamount - Lindsay, Ronald; Kwok, Ronald; de Steur, Laura; Meier, Walt (Geophysical Research Letters, 2008)
A distinctive halo of sea ice deformation was observed above the Maud Rise seamount in the eastern Weddell Sea in the winter of 2005. The deformation halo is coincident with a halo of low mean ice concentration that is often observed in the region. Monthly mean ice vorticity estimates for the months July through November reveal the deformation zone most clearly in an arc about 100 km northwest of the seamount where there is a strong gradient in the bathymetry at depths of 3000–5000 m. The deformation was computed from satellite-based ice motion vectors derived from Envisat Synthetic Aperture Radar backscatter images. The deformation halo is evidence of a Taylor cap circulation over the seamount, which has been described and analyzed with modeling studies and concurrent oceanographic observations obtained during an extensive field campaign.
Keywords: Sørishavet; Weddellhavet; havis; havstrømmer; hydrografi; oseanografi; sjøis; vannvirvler

Wintertime ocean conditions over the southern Weddell Sea continental shelf, Antarctica - Nicholls, Keith W; Boehme, Lars; Biuw, Martin; Fedak, Michael A (Geophysical Research Letters, 2008)
During the austral winter of 2007 a Weddell Seal tagged with a miniaturized conductivity-temperature-depth (CTD) instrument travelled over the central southern Weddell Sea continental shelf. The instrument yielded 750 CTD profiles, 250 of them to the sea floor. The data show a full depth flow of water onto the shelf via a sill at the shelf break (74°S 44°W). The warmth from the core of the flow was able to maintain the surface mixed layer above the freezing point, resulting in a band of reduced ice-production. An estimate of the on-shelf flux suggests that this flow accounts for most of the estimated 3 Sv of water draining from the southern Weddell Sea continental shelf.
Keywords: Sørishavet; Weddellhavet; kontinentalsokkel; marin zoologi; oseanografi; saltinnhold; seler; temperatur

Hilsen fra Sørishavet - Pedersen, Ronald (Berlevågingen, 2008)
Keywords: Sørishavet; forskning; krill; marinbiologi; teknologi

Comparison of contemporary and fossil diatom assemblages from the western Antarctic Peninsula shelf - Pike, Jennifer; Allen, Claire S.; Leventer, Amy; Stickley, Catherine E.; Pudsey, Carol J. (Marine Micropaleontology, 2008)
During the past ten years, the Antarctic Peninsula has been identified as the most rapidly warming region of the Southern Hemisphere and it is important to place this warming in the context of the natural climate and oceanographic variability of the recent geological past. Many biological proxies, such as marine diatom assemblages, have been used to determine Southern Ocean palaeoceanographic conditions during the Late Quaternary, however, few investigations have attempted to link observations of modern floras with the fossil record. In this study we examine a suite of modern austral spring (December 2003) and summer (February 2002) surface water samples from along the western Antarctic Peninsula (WAP) continental shelf and compare these to core-top, surface sediment samples. Using detrended correspondence analysis (DCA) and principal component analysis (PCA) of diatom abundance data we investigate the relationship of contemporary diatom floras with the fossil record. This multivariate analysis reveals that our modern assemblages can be divided into three groups: summer southern WAP sites, summer northern WAP sites, and spring WAP sites. Sea surface temperature (SST) is an important environmental variable for explaining seasonal differences in diatom assemblages between spring and summer, but sea surface salinity (SSS) is more important for understanding temporally-equivalent regional variations in assemblage. Our summer diatom samples are more reminiscent of early season assemblages, reflecting the unusually late sea ice retreat from the region that year. When the modern assemblages are compared to the fossil record, it is clear that most of the important diatoms from the summer assemblage are not preserved into the sediments, and that the fossil record more closely reflects spring assemblages. This observation is important for any future attempts to quantitatively reconstruct palaeoceanographic conditions along the WAP during the Late Quaternary and highlights the need for many more such studies in order to address longer timescales, such as interannual variability, in the context of the fossil record.
Keywords: Sørishavet; Vestantarktis; diatomeer; marin biologi; marin geologi; mikropaleontologi; paleoseanografi

The Cosmonaut Sea Wedge - Solli, Kenneth; Kuvaas, Berit; Kristoffersen, Yngve; Leitchenkov, German; Guseva, J; Gandyukhin, V (Marine Geophysical Researches, 2008)
Keywords: Sørishavet; kontinentalmargin; marin geofysikk; sedimenter

Blocking primers to enhance PCR amplification of rare sequences in mixed samples – a case study on prey DNA in Antarctic krill stomachs - Vestheim, Hege; Jarman, Simon N. (Frontiers in Zoology, 2008)
Identification of DNA sequence diversity is a powerful means for assessing the species present in environmental samples. The most common molecular strategies for estimating taxonomic composition depend upon PCR with universal primers that amplify an orthologous DNA region from a range of species. The diversity of sequences within a sample that can be detected by universal primers is often compromised by high concentrations of some DNA templates. If the DNA within the sample contains a small number of sequences in relatively high concentrations, then less concentrated sequences are often not amplified because the PCR favours the dominant DNA types. This is a particular problem in molecular diet studies, where predator DNA is often present in great excess of food-derived DNA.
Keywords: Scotiahavet; Sørishavet; genetikk; genetisk analyse; krill; marin biologi; plankton; taksonomi